PROTEUS SYNDROME: A RARE DISEASE OF DISPROPORTIONATE AND ASYMMETRIC OVERGROWTH OF CONNECTIVE TISSUE - Qaisar, Fahad; Butt, Nauman Ismat; Ghoauri, Muhammad Sohail Ajmal; Azhar, Madiha; Javed, Muhammad Umair; Samad, Abdul (Journal of Ayub Medical College Abbottabad, 2023)
Proteus syndrome is a rare disease manifested by progressive segmental overgrowth involving the skeletal, Cutaneous, subcutaneous, and nervous systems. We report the case of a 24-year-old female who was born with no obvious abnormality at birth. From the age of 1’‰year, she developed asymmetric enlargement of her left upper limb and bilateral lower limbs leading to enlargement of the right-hand phalanges with radial deviation, enlargement of the right big toe, lateral deviation of left foot, and discrepancy in the length of lower extremities and kyphoscoliosis. She had become bed-bound for the last few years due to increasing disability. She was diagnosed with Proteus syndrome based on clinical features of progressive course, mosaic distribution, and sporadic occurrence of the lesions.